ANALISIS SALURAN DAN EFEKTIVITAS PEMASARAN TEMBAKAU DI SUKABUMI, CEPOGO, BOYOLALI - Hesti Widyaningsih; Novindra Novindra (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
Tobacco is a leading commodity in Cepogo District, especially chopped tobacco in Sukabumi Village. Tobacco farming is interesting in terms of marketing, there are many tobacco traders or middlemen so that the institutions and marketing channels that are traversed by farmers are different. The nature of this tobacco is a fancy product, meaning that farmers do not know the quality of the tobacco produced so that farmers are in an unfavorable bargaining position. Therefore, this study aims to (1) identify marketing channels and marketing functions in each tobacco marketing agency, (2) analyze the efficiency of tobacco marketing channels. The method used in this research is descriptive qualitative analysis, marketing margin analysis, farmer's share, and profit to cost ratio. The results of the study show that the pattern of marketing channel 4 is the most efficient compared to other marketing channels. Marketing channel 4 pattern has a marketing margin of 0 rupiah, a farmer's share of 100 percent, and a profit and cost ratio of 5,98.